Integrating isotopic niche metrics and gut microbiota assembly reveals coexistence mechanisms in subtropical riverine fish - Yaqiu Liu; Xinhui Li; Konstantinos Ar. Kormas; Chunni Kou; Huifeng Li; Yuefei Li; Jie Li (Ecological Informatics)
Understanding interspecific niche overlap is fundamental for evaluating resource partitioning and competitive interactions among sympatric species. Microbial symbiont facilitates rapid adaptation to novel ecological niches, substantially augmenting host evolutionary fitness and ecological success. Nevertheless, the mechanisms through which host-microbe symbiosis mediates fish coexistence patterns in subtropical riverine ecosystems remain incompletely understood. This investigation employed stable carbon (δ13C) and nitrogen (δ15N) isotope analysis to quantify trophic niche width and overlap among seven sympatric fish species in the Yuanjiang River ecosystem, complemented by high-throughput sequencing of gut microbial communities. Our results showed that host phylogenetic specificity primarily reflected the similarity in deterministic selection processes (host filtering) mediated by host phylogenetic conservatism. Comprehensive β-diversity analyses consistently confirmed phylosymbiosis patterns across multiple community metrics. Moreover, stochastic processes, including dispersal limitation and drift, also played an important role in shaping the exact composition of gut microbial communities within specific host individuals. Furthermore, our findings indicated fish host trophic niche differentiation emerges as an essential adaptive mechanism facilitating interspecific coexistence by minimizing resource competition. Crucially, we identified the similarity of the intestinal microbial community structure is closely related to the degree of overlap of its nutritional ecological niche, indicating functional convergence between host trophic niches and their symbiotic microbiomes.These microbial adaptations facilitate nutritional optimization from varied trophic sources, mediate interspecific resource partitioning, and expand ecological opportunities within the fish community. Our integrative analysis identifies host-microbiome symbiosis as an evolutionary innovation. Through this mechanism, niche expansion and competitive coexistence are enhanced in subtropical river ecosystems.